Fireproof and mildewproof dealcoholized one-component silicone sealant and preparation method thereof

CN122941346APending Publication Date: 2026-10-20GUANGDONG GAOSHI GAOKE IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611394020.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

已有技术尝试通过硅烷偶联剂对无机填料进行表面包覆,但此类包覆仅着眼于分散性改善,未能同时解决填料活性位点对催化剂的毒化问题及对防霉剂的消耗问题

Benefits of technology

(1)本发明通过在硼酸锌核层中掺杂Ag+和/或Cu2+,使密封胶的成瓷起始温度降至400℃以下,400℃烧蚀后弯曲强度达到3.0MPa以上,阻燃等级达FV-0至FV-1级,实现了低温条件下快速形成结构完整的陶瓷层,克服了传统陶瓷化技术成瓷温度过高的缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention relates to a fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant and its preparation method, belonging to the technical field of organosilicon sealants. Existing alcohol-free type silicone sealants struggle to simultaneously achieve fire resistance, mildew resistance, storage stability, and rapid curing. The sealant comprises a core-shell functional filler, which, from the inside out, includes components doped with Ag. + and / or Cu 2+ The product consists of a zinc borate core layer, a functional shell formed by the co-condensation of polyether-modified silane and KH-560, and a reactive quaternary ammonium salt chemically grafted onto the surface of the functional shell. The reactive quaternary ammonium salt anchors the phosphorus-containing ionic liquid through ion-pair interactions. It is doped with Ag. + and / or Cu 2+ The zinc borate core layer forms a ceramic layer at high temperatures to achieve fire resistance, while the functional shell layer provides catalytic protection and rapid curing. The reactive quaternary ammonium salt provides long-lasting anti-mildew properties, and the phosphorus-containing liquid synergistically enhances flame retardant performance with the zinc borate core layer. This sealant is suitable for sealing joints in indoor kitchens, bathrooms, balconies, and other home decoration scenarios.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organosilicon sealant technology, specifically relating to a fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant and its preparation method. Background Technology

[0002] Silicone sealants, due to their excellent weather resistance, temperature resistance, and elasticity, have been widely used in sealing applications such as building doors and windows, kitchen and bathroom joints, and interior decoration. With increasing demands for indoor safety and health, silicone sealants must simultaneously meet comprehensive requirements for environmental friendliness, mildew resistance, and fire safety. One-component, alcohol-free silicone sealants, which release small alcohol molecules during curing, are non-toxic, odorless, and non-corrosive to the substrate, have become the mainstream choice for this application.

[0003] To achieve fire resistance, existing technologies typically add flame-retardant fillers such as aluminum hydroxide and magnesium hydroxide, or ceramic fillers such as low-melting-point glass powder and zinc borate, to form a ceramic layer in the colloid at high temperatures to block flames. However, the surfaces of these fillers are rich in active hydroxyl groups and surface active sites, which strongly adsorb the titanium-based catalysts widely used in dealcoholized silicone sealants. This leads to the catalyst's active centers being captured by the filler surface, resulting in poisoning and reducing the storage stability and curing rate of the silicone sealant.

[0004] Meanwhile, to impart anti-mildew properties to silicone sealants, existing technologies often employ physical blending to add cationic anti-mildew agents such as quaternary ammonium salts. However, these anti-mildew agents are prone to electrostatic adsorption or ion exchange with inorganic fillers in the system, becoming fixed on the filler surface and unable to effectively disperse in the colloidal matrix, resulting in a significant reduction in actual anti-mildew efficacy.

[0005] Furthermore, dealcohol-type one-component silicone sealants require catalysts to remain active during storage, while simultaneously needing both catalysts and efficient curing during application. In existing technologies, while physical coating to isolate the catalyst can improve storage stability, excessively thick coatings hinder contact between the catalyst and crosslinking agents and moisture during application, leading to delayed curing; conversely, coatings that are too thin cannot effectively prevent catalyst poisoning during storage. Therefore, achieving rapid curing during application while protecting catalyst activity is one of the core technical challenges facing dealcohol-type one-component silicone sealants. Existing technologies have attempted to surface-coat inorganic fillers with silane coupling agents, but such coatings only focus on improving dispersibility and fail to simultaneously address the problems of catalyst poisoning at filler active sites and the consumption of antifungal agents.

[0006] In summary, existing de-alcoholized one-component silicone sealants cannot simultaneously achieve fire resistance, mildew resistance, storage stability, and rapid curing. These problems are interconnected, and a systematic technical solution to resolve these contradictions is urgently needed. Summary of the Invention

[0007] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant and its preparation method. The specific technical solution is as follows: In a first aspect, the present invention provides a fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant, comprising the following components by weight: 100 parts of alkoxy-terminated polydimethylsiloxane, 10-20 parts of MDT branched silicone oil, 20-40 parts of core-shell functional filler, 25-45 parts of reinforcing filler, 0.5-2 parts of phosphorus-containing ionic liquid, 2-8 parts of crosslinking agent, 0.5-2 parts of titanium-based chelate catalyst, 0.5-5 parts of silane coupling agent, and 0.5-3 parts of hydroxyl scavenger; The phosphorus-containing ionic liquid is 1-ethyl-3-methylimidazolium dibutyl phosphate; the core-shell functional filler, from the inside out, comprises Ag-doped components. + and / or Cu 2+ The core consists of a zinc borate core and a functional shell coating the surface of the core. The functional shell is formed by copolymerization of polyether-modified silane and KH-560, wherein KH-560 provides chemical bonding and effective coating to the surface of the core; the polyether-modified silane provides surface hydrophilicity; and the surface of the functional shell is chemically grafted with a reactive quaternary ammonium salt.

[0008] Under high-temperature fire conditions, the zinc borate core layer undergoes thermal degradation, releasing B2O3. The B2O3 melts into a liquid phase at high temperatures, wetting and binding SiO2 and other inorganic fillers generated from the decomposition of polydimethylsiloxane in the system. Liquid-phase sintering promotes the formation of the ceramic layer. The core layer is doped with Ag. + and / or Cu 2+ It participates in the ceramization process at high temperatures, and as a nucleation promoting component, it reduces the nucleation activation energy of the B2O3-SiO2 glass phase, thereby lowering the ceramization initiation temperature to around 400℃ and below, thus achieving low-temperature ceramization fireproofing.

[0009] Meanwhile, the phosphorus-containing compounds released from the decomposition of phosphorus-containing ionic liquid react with B2O3 to form a low-melting-point boron-phosphorus glass phase. This glass phase can form a continuous liquid phase below 400℃, filling microcracks in the ceramic layer and improving the structural integrity and mechanical properties of the ceramic layer. Furthermore, the phosphorus-containing free radicals generated from the decomposition of phosphorus-containing ionic liquid can quench gas-phase combustion chain reactions, forming a ternary synergistic flame-retardant system with the condensed phase ceramic-forming effect of zinc borate and the nitrogen-based expansion flame-retardant effect of quaternary ammonium salt.

[0010] During room temperature storage, the functional shell layer forms a coating layer due to the reaction of KH-560 with the hydroxyl groups on the surface of the zinc borate core layer. This passivates the active sites on the core layer surface, preventing them from contacting the titanium-based chelate catalyst, thus avoiding catalyst adsorption and poisoning and ensuring storage stability. During use, the polyether hydrophilic segments of the polyether-modified silane can improve the wetting and penetration kinetics of water on the surface of the functional shell layer, promote the enrichment and inward diffusion of water molecules at the interface, thereby accelerating the de-alcoholization crosslinking reaction and achieving rapid deep curing.

[0011] The reactive quaternary ammonium salt chemically grafted onto the surface of the functional shell is covalently fixed to the outermost layer of the core-shell functional filler, without free migration or ion exchange with the zinc borate in the core layer; after curing, the reactive quaternary ammonium salt is distributed on the surface of the sealant, giving the sealant long-lasting anti-mildew properties through contact sterilization.

[0012] Preferably, in the zinc borate core layer, Ag + The doping amount is Zn 2+ 0.5-3% molar amount of Cu 2+ The doping amount is Zn 2+ The molar amount is 1-5%. If the doping amount is below this range, the heterogeneous nucleation effect is not obvious and the ceramic temperature decreases only slightly. If the doping amount is above this range, the stability of the zinc borate lattice structure decreases, affecting the ceramicization ability of the core-shell functional filler itself.

[0013] Preferably, the particle size of the zinc borate core layer is 1~10 μm. When the particle size is less than 1 μm, the specific surface area of ​​the zinc borate core layer is too large, resulting in too many surface active sites, which increases the difficulty of functional shell coating and the potential poisoning risk of titanium-based chelate catalysts. When the particle size is greater than 10 μm, the specific surface area of ​​the zinc borate core layer is too small, resulting in insufficient B2O3 release and reduced efficiency, which is not conducive to the ceramicization effect.

[0014] Preferably, the polyether-modified silane is prepared by a ring-opening reaction of a terminal epoxy polyether and an aminosilane, wherein the molecular weight of the terminal epoxy polyether is 400-2000, and the aminosilane is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

[0015] Preferably, the reactive quaternary ammonium salt is a quaternary ammonium salt containing alkoxysilane groups, and chemical grafting is achieved by condensation of the alkoxysilane groups with residual hydroxyl groups on the surface of the functional shell; the reactive quaternary ammonium salt is 3-(trimethoxysilyl)propyldimethyloctadecylammonium chloride.

[0016] Preferably, the anions of the phosphorus-containing ionic liquid and the reactive quaternary ammonium salt cations grafted onto the surface of the functional shell layer form ion pairs on the surface of the core-shell functional packing, anchoring the phosphorus-containing ionic liquid to the surface of the core-shell functional packing. The formation of the ion pairs is based on electrostatic interaction, which can inhibit the diffusion of the phosphorus-containing ionic liquid to the catalyst during storage, avoid coordination poisoning of the titanium chelate catalyst by phosphorus compounds, and at the same time, the phosphorus-containing ionic liquid can reduce the surface tension of the core-shell functional packing, improving the dispersibility of the packing in the sealant.

[0017] Preferably, the amount of phosphorus-containing ionic liquid added is 0.5 to 2 parts. If it is below this range, the flame retardant synergistic effect will not be obvious, and if it is above this range, the mechanical properties of the sealant may be damaged due to excessive ionic liquid.

[0018] Preferably, the alkoxy-terminated polydimethylsiloxane has a viscosity of 5000~80000 mPa·s at 25°C.

[0019] Preferably, in the MDT branched silicone oil, the M-chain segment is (CH3)3SiO. 1 / 2 The D-chain unit is (CH3)2SiO 2 / 2 The T-linker is CH3SiO 3 / 2 The viscosity of the MDT branched silicone oil is 100~2000 mPa·s.

[0020] Preferably, the reinforcing filler is fumed silica and / or precipitated silica with a specific surface area of ​​100~400 m². 2 / g.

[0021] Preferably, the crosslinking agent is selected from at least one of methyltrimethoxysilane, phenyltrimethoxysilane, tetraethyl orthosilicate and its oligomers.

[0022] Preferably, the titanium-based chelate catalyst is diisopropoxybis(acetylacetone)titanium, diisopropoxybis(ethylacetoacetic acid)titanium, or a chelate of tetrabutyl titanate and acetylacetone.

[0023] Preferably, the silane coupling agent is selected from at least one of γ-glycidoxypropyltrimethoxysilane and γ-methacryloyloxypropyltrimethoxysilane.

[0024] Preferably, the hydroxyl scavenger is selected from at least one of hexamethyldisilazane, trimethylchlorosilane, and vinyltrimethoxysilane.

[0025] Secondly, the present invention provides a method for preparing a core-shell functional packing material, comprising the following steps: (1) Disperse zinc borate in silver salt and / or copper salt solutions, carry out ion exchange reaction, and obtain Ag-doped products by washing, drying and grinding. +and / or Cu 2+ The zinc borate core layer; (2) Disperse the zinc borate core layer obtained in step (1) in an alcohol-water mixed solvent, add polyether-modified silane and KH-560, carry out hydrolysis and condensation reaction, and after washing, drying and grinding, obtain a functional shell layer coated on the surface of the zinc borate core layer. (3) Disperse the functional shell obtained in step (2) in an organic solvent, add a reactive quaternary ammonium salt, carry out a grafting reaction, and after washing, drying and grinding, obtain a core-shell functional filler with a reactive quaternary ammonium salt chemically grafted on the surface of the functional shell. Preferably, in step (1), the temperature of the ion exchange reaction is 30~80℃ and the time is 2~8 hours.

[0026] Preferably, in step (1), the silver salt is silver nitrate, and the copper salt is copper nitrate, copper sulfate, or copper chloride.

[0027] Preferably, in step (2), the polyether-modified silane is prepared by ring-opening reaction of terminal epoxy polyether and aminosilane; the molar ratio of polyether-modified silane to KH-560 is (0.3~2):1; if the proportion of KH-560 is too low, the cross-linking density of the functional shell is insufficient, and it cannot effectively block the contact between the active sites of the titanium chelate catalyst and the zinc borate core layer; if the proportion of KH-560 is too high, the content of hydrophilic segments of polyether is insufficient, and the water absorption and curing effect is weakened.

[0028] Preferably, in step (2), the temperature of the hydrolysis-condensation reaction is 40~80℃ and the time is 2~6 hours; the volume ratio of alcohol to water in the alcohol-water mixed solvent is (3~5):1.

[0029] Preferably, in step (3), the grafting reaction is carried out at a temperature of 50-100°C for 4-12 hours; the organic solvent is ethanol, isopropanol or acetone.

[0030] Thirdly, the present invention provides a method for preparing a fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant, comprising the following steps: S1. Add alkoxy-terminated polydimethylsiloxane, MDT branched silicone oil, core-shell functional filler and reinforcing filler to a kneader, mix and dehydrate under vacuum conditions, and cool to room temperature to obtain the base material; S2. Under inert gas protection, add crosslinking agent, silane coupling agent and hydroxyl scavenger to the base material obtained in step S1, and mix evenly; S3. Add phosphorus-containing ionic liquid and stir at 30~50℃ for 0.5~1 hours to form ion pairs between the anions of the phosphorus-containing ionic liquid and the reactive quaternary ammonium salt cations chemically grafted onto the surface of the core-shell functional packing, thereby anchoring the phosphorus-containing ionic liquid onto the surface of the core-shell functional packing. S4. Add titanium-based chelate catalyst, continue stirring under vacuum, discharge and fill to obtain fireproof, mildew-proof, alcohol-free type one-component silicone sealant.

[0031] Preferably, the temperature of the mixing and dehydration in step S1 is 100~150℃, the time is 2~4 hours, and the vacuum degree is -0.08~-0.095 MPa.

[0032] Preferably, the inert gas in step S2 is nitrogen.

[0033] Preferably, in step S2, the mixing is carried out at 20~40°C for 10~40 minutes.

[0034] Preferably, in step S3, the stirring is carried out under normal pressure or slightly negative pressure conditions.

[0035] Preferably, the stirring time in step S4 is 0.5 to 2 hours, and the vacuum degree is -0.08 to -0.095 MPa.

[0036] Compared with the prior art, the present invention has the following advantages: (1) The present invention involves doping Ag into the zinc borate core layer. + and / or Cu 2+ This reduces the ceramic initiation temperature of the sealant to below 400℃, and the flexural strength after ablation at 400℃ reaches over 3.0MPa. The flame retardant rating reaches FV-0 to FV-1, enabling the rapid formation of a structurally complete ceramic layer under low-temperature conditions and overcoming the defect of excessively high ceramic initiation temperature in traditional ceramicization technology.

[0037] (2) The present invention coats the surface of the zinc borate core layer with a functional shell layer formed by the co-condensation of polyether-modified silane and KH-560. KH-560 reacts with the hydroxyl groups on the surface of the core layer to form a coating, which blocks the active sites on the surface of the core layer from contacting the titanium chelate catalyst and avoids the catalyst being adsorbed and poisoned. The polyether hydrophilic segments of the polyether-modified silane promote the enrichment and inward diffusion of water molecules at the interface, making the surface drying time change rate as low as 8.3% and the deep curing depth of 24h reach more than 4.5mm, thus achieving storage stability and rapid curing.

[0038] (3) The present invention chemically grafts reactive quaternary ammonium salts onto the surface of the functional shell layer, so that the reactive quaternary ammonium salts are covalently fixed to the outermost layer of the core-shell functional filler without migration or loss. After 120 days of anti-mildew test, it still maintains the anti-mildew level of 0, thus achieving long-term anti-mildew effect.

[0039] (4) By adding phosphorus-containing ionic liquid, the present invention utilizes the anions of the ionic liquid to form ion pairs with the reactive quaternary ammonium salt cations grafted on the surface of the functional shell to anchor the ionic liquid on the filler surface, thus avoiding the poisoning of titanium catalyst by phosphorus compounds. At high temperature, the phosphorus-containing compounds released by the decomposition of the ionic liquid react with B2O3 to generate a low-melting-point boron-phosphorus glass phase, which fills the microcracks in the ceramic layer, thus realizing the ternary synergistic flame retardancy of phosphorus-containing ionic liquid, zinc borate and quaternary ammonium salt. Detailed Implementation

[0040] To more clearly illustrate the present invention, the following description, in conjunction with embodiments and comparative examples, further clarifies the invention. Those skilled in the art should understand that the following description represents preferred embodiments of the invention, but the invention is not limited to these embodiments.

[0041] I. Preparation Example Preparation Example 1: Ag + Doped core-shell functional fillers 100 g of zinc borate (particle size 3-5 μm, molecular weight approximately 434.6 based on 2ZnO·3B2O3·3.5H2O) was dispersed in 500 mL of 0.05 mol / L silver nitrate solution (containing approximately 4.25 g AgNO3). The mixture was stirred in a 60 °C water bath for 4 hours, centrifuged, washed three times with deionized water, dried at 100 °C for 2 hours, ground, and sieved to obtain AgNO3. + Doped zinc borate core layer (Ag) + The doping amount is Zn 2+ (1.5% of the molar weight).

[0042] The above-mentioned doped zinc borate was dispersed in 400 mL of alcohol-water mixed solvent (ethanol:water = 4:1, volume ratio), and a compound of 4.2 g of polyether modified silane (molecular weight about 1000, prepared by ring-opening reaction of terminal epoxy polyether and γ-aminopropyltriethoxysilane) and 0.8 g of KH-560 (molar ratio 1.2:1, total 5 g) was added. The pH was adjusted to 5-6 with acetic acid, and the mixture was stirred at 60 °C for 4 hours. After centrifugation, the mixture was washed three times with ethanol, dried at 100 °C for 2 hours, ground and sieved to obtain the functional shell layer coated on the surface of the zinc borate core layer.

[0043] The above-mentioned coated product was dispersed in 300 mL of ethanol, and 5 g of 3-(trimethoxysilyl)propyldimethyloctadecylammonium chloride was added. The mixture was stirred at 75 °C for 8 hours, centrifuged, washed three times with ethanol, dried at 100 °C for 2 hours, ground and sieved to obtain the core-shell functional filler.

[0044] Preparation Example 2: Cu 2+ Doped core-shell functional fillers (1) Replace silver nitrate with copper nitrate (Cu(NO3)2·3H2O 6.04g, dissolved in 500mL deionized water, concentration 0.05mol / L), otherwise the same as step (1) of preparation example 1, to obtain Cu 2+ Doped zinc borate core layer (Cu) 2+ The doping amount is Zn 2+ (3% of the molar weight).

[0045] Steps (2) to (3) of this preparation example are the same as steps (2) to (3) of preparation example 1.

[0046] Preparation Example 3: Ag + and Cu 2+ Co-doped core-shell functional fillers (1) Add silver nitrate (2.12g, Ag) + Concentration 0.025 mol / L) and copper nitrate (Cu(NO3)2·3H2O 6.04 g, Cu 2+ The 0.05 mol / L solution was dissolved together with 500 mL of deionized water, and the rest of the steps were the same as in Preparation Example 1 (1) to obtain Ag. + / Cu 2+ Co-doped zinc borate core layer (Ag) + The doping amount is Zn 2+ 1.5% molar amount of Cu 2+ The doping amount is Zn 2+ (3% of the molar weight).

[0047] Steps (2) to (3) of this preparation example are the same as steps (2) to (3) of preparation example 1.

[0048] Preparation Example 4: Ag Doping + Uncoated and ungrafted fillers (1) Same as step (1) in Preparation Example 1, to obtain Ag + Doped with zinc borate core layer. Step (2) functional shell coating and step (3) reactive quaternary ammonium salt grafting are not performed.

[0049] Preparation Example 5: KH-560 Coated Ungrafted Filler Only (1) Same as step (1) in preparation example 1.

[0050] (2) The zinc borate core layer obtained in step (1) was dispersed in 400 mL of alcohol-water mixed solvent (ethanol:water = 4:1, volume ratio), 5 g of KH-560 (excluding polyether-modified silane) was added, the pH was adjusted to 5-6 with acetic acid, the mixture was stirred at 60 °C for 4 hours, centrifuged, washed 3 times with ethanol, dried at 100 °C for 2 hours, ground and sieved to obtain KH-560-coated zinc borate. The reactive quaternary ammonium salt grafting in step (3) was not performed.

[0051] Preparation Example 6: Polyether-modified silane-coated grafted filler (1) Same as step (1) in preparation example 1.

[0052] (2) Disperse the zinc borate core layer obtained in step (1) in 400 mL of alcohol-water mixed solvent (ethanol:water = 4:1, volume ratio), add 5 g of polyether modified silane (excluding KH-560), adjust the pH to 5-6 with acetic acid, stir at 60°C for 4 hours, centrifuge, wash 3 times with ethanol, dry at 100°C for 2 hours, grind and sieve to obtain polyether modified silane coated zinc borate.

[0053] Step (3) in this preparation example is the same as step (3) in preparation example 1.

[0054] Preparation Example 7: Functional Shell Non-grafted Reactive Quaternary Ammonium Salt Filler Steps (1) to (2) in this preparation example are the same as steps (1) to (2) in preparation example 1. The reactive quaternary ammonium salt grafting in step (3) is not performed.

[0055] Preparation Example 8: Ag + Overdoped core-shell functional fillers (1) Increase silver nitrate to 16.99 g (dissolved in 500 mL of deionized water, concentration 0.2 mol / L), and follow the same procedure as in Preparation Example 1 (1) to obtain Ag. + Excessive doping of zinc borate core layer (Ag) + The doping amount is Zn 2+ (6% of the molar weight).

[0056] Steps (2) to (3) of this preparation example are the same as steps (2) to (3) of preparation example 1.

[0057] Preparation Example Test Method The core layer particle size was determined using a laser particle size analyzer: The zinc borate core layer powder obtained in step (1) (before functional shell coating) was dispersed in deionized water and ultrasonically dispersed for 5 min. The particle size distribution was then determined using a laser particle size analyzer. D 50 This indicates the average particle size.

[0058] The chemical composition of the functional shell was analyzed using Fourier transform infrared spectroscopy (FTIR): Core-shell functional filler powder was prepared and analyzed using the KBr pellet method, with a scanning range of 4000–400 cm⁻¹. -1 .

[0059] The content of organic matter in the functional shell was analyzed using a thermogravimetric analyzer (TGA): core-shell functional filler powder was taken and heated from room temperature to 800℃ at a heating rate of 10℃ / min in air atmosphere, and the mass loss of the sample was recorded as a function of temperature.

[0060] The contents of Ag and Cu in the ablation residue were determined by atomic absorption spectrometry (AAS): Core-shell functional filler powder was ablated at 400℃ for 30 min. The ablation residue powder was then digested with aqua regia by heating. After adjusting the volume, the contents of the metal elements in the solution were quantitatively determined by atomic absorption spectrophotometer at the corresponding characteristic wavelengths (Ag: 328.1 nm, Cu: 324.7 nm) using the standard curve method.

[0061] The test data for the preparation example are shown in Table 1: Table 1

[0062] Note: "-" indicates that the corresponding element was not doped in this preparation example, so its content was not measured.

[0063] Results Analysis Zinc borate core particle size: The core particle size of each preparation example was in the range of 2.9~3.3μm, meeting the requirement of 1~10μm, indicating that Ag + and / or Cu 2+ The co-doping process did not have a significant effect on the particle size of the zinc borate core layer.

[0064] FTIR: The infrared spectra of preparation examples 1, 2, 3, 6, and 8 are approximately 1100 cm⁻¹. -1 Characteristic absorption peaks of polyether COC were observed at approximately 1080 cm⁻¹. -1 The characteristic absorption peak of Si-O-Si appears at approximately 1480 cm⁻¹, and also at approximately 1480 cm⁻¹. -1 CN appears at [location] + The characteristic absorption peaks indicate that the functional shell has been successfully coated onto the surface of the zinc borate core. In Preparation Example 4, since no functional shell coating was performed, neither of the above two characteristic peaks appeared in the infrared spectrum. Preparation Example 5, coated only with KH-560, showed a Si-O-Si characteristic absorption peak but no polyether COC characteristic absorption peak, indicating that its functional shell does not contain polyether segments. Preparation Example 6, coated only with polyether-modified silane, showed both polyether COC and Si-O-Si characteristic absorption peaks, indicating that polyether-modified silane can also form a functional shell structure through self-condensation. Although Preparation Example 7 has a complete functional shell, because reactive quaternary ammonium salt grafting was not performed, no CN was observed in its infrared spectrum. + Characteristic absorption peaks.

[0065] TGA: Preparations 1-3, 6, and 8 exhibited a weight loss step from organic matter decomposition within the temperature range of 300-500℃, with weight loss rates between 7.8% and 8.5%. Preparation 4, lacking a functional shell coating, showed a weight loss rate of only 0.5%. Preparation 5, with only KH-560 coating, had a weight loss rate of 3.2%. Preparation 7, without quaternary ammonium salt grafting, showed a weight loss rate of 5.5%, indicating that quaternary ammonium salts increased the organic matter content in the functional shell. These results further corroborate the analytical conclusions of FTIR.

[0066] Atomic absorption spectrometry (AAS): The Ag and Cu contents of the residues after ablation in Preparation Examples 1 and 3 were in the ranges of 1800–1900 ppm and 2000–2200 ppm, respectively, indicating that silver and copper elements were indeed present in the residues after ablation. This suggests that the doped Ag and Cu remained in the residues after high-temperature ablation and participated in the ceramization process. Preparation Example 8, with an Ag doping amount of 6%, had an Ag content of 7300 ppm in the residue after ablation, far exceeding the 1850 ppm of Preparation Example 1.

[0067] II. Sealant Preparation Method S1. Add alkoxy-terminated polydimethylsiloxane, MDT branched silicone oil, core-shell functional filler and reinforcing filler to a kneader, mix and dehydrate at 120℃ and vacuum degree -0.09MPa for 3 hours, and cool to room temperature.

[0068] S2. Under nitrogen protection, add crosslinking agent (methyltrimethoxysilane, 5 parts), silane coupling agent (KH-560, 3 parts) and hydroxyl scavenger (vinyltrimethoxysilane, 2 parts), and mix thoroughly at 30°C for 30 minutes.

[0069] S3. Add phosphorus-containing ionic liquid (1-ethyl-3-methylimidazolium dibutyl phosphate, 1 part), and stir for 0.5 hours at 40°C under slight negative pressure to allow the ionic liquid to form ion pairs with the quaternary ammonium salt grafted on the surface of the core-shell functional filler for anchoring.

[0070] S4. Finally, add the titanium chelate catalyst, stir for 1 hour under a vacuum of -0.09MPa, discharge and fill to obtain the fireproof, mildew-proof, alcohol-free type one-component silicone sealant.

[0071] The formulations for the embodiments are shown in Tables 2 and 3: Table 2 Formulations of Examples 1-5

[0072] Table 3 Formulations of Examples 6-11

[0073] The scale settings are shown in Table 4: Table 4. Setting the Comparison Scale

[0074] Test methods Fire resistance performance test (1) Ceramization initiation temperature The sealant was poured into a 20mm×10mm×2mm mold and cured for 7 days under standard conditions (23±2℃, RH50±5%). The sample was placed in a muffle furnace and heated from room temperature at a rate of 10℃ / min. The condition of the sample was observed in real time through the observation window, or a sample was taken out for observation every 20℃. When a hard, structurally complete ceramization layer began to appear on the sample surface, and light touching with tweezers did not produce obvious deformation or powder falloff, the temperature at which this occurred was recorded as the ceramization initiation temperature.

[0075] (2) Bending strength after ablation at 400℃ The sealant was poured into an 80mm × 10mm × 4mm mold and cured for 7 days under standard conditions. The sample was placed in a muffle furnace and heated to 400℃ at a rate of 10℃ / min, held at that temperature for 30 minutes, and then cooled to room temperature with the furnace. The ablated sample was removed and subjected to a three-point bending test using a universal testing machine. The span between the support points was 30mm, and the loading head was positioned directly above the midpoint of the span. Pressure was applied at a loading rate of 5mm / min until the sample fractured. The maximum load was recorded and calculated using the formula σ = 3FL / (2bh). 2 Calculate the bending strength, where F is the maximum load (N), L is the span between supports (mm), b is the specimen width (mm), and h is the specimen thickness (mm). Test 5 specimens in each group and take the arithmetic mean.

[0076] (3) Vertical combustion rating Refer to Method A (Vertical Burning Method) of GB / T 10707-2008 "Determination of Burning Performance of Rubber". Pour the sealant into a 130mm×13mm×3mm mold and cure for 7 days under standard conditions. Fix the sample vertically in a burning test chamber and burn it with a Bunsen burner (flame height 20mm) at the center of the lower end of the sample for 10 seconds, then remove the burner. Record the flaming burning time t1. After the sample self-extinguishes after the flame is removed, immediately re-ignite for 10 seconds, recording the flaming burning time t2 and the flameless burning time t3. Test 5 samples per group and evaluate them according to the standard as FV-0, FV-1, or FV-2.

[0077] (4) Limiting oxygen index test The test was conducted according to GB / T 2406.2-2009, "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test". The sealant was poured into an 80mm × 10mm × 4mm mold and cured for 7 days under standard conditions (23±2℃, RH 50±5%). The sample was vertically fixed in the combustion chamber of the oxygen index tester. The flow rate and oxygen concentration of the oxygen-nitrogen mixture were adjusted, and the top of the sample was ignited. The combustion behavior of the sample was observed. The lowest oxygen concentration at which the sample extinguished within 3 minutes or the burning length did not exceed 50mm was taken as the limiting oxygen index. Five samples were tested in each group, and the arithmetic mean was taken.

[0078] (5) Elemental analysis after ablation The sealant samples from Example 3 and Comparative Example 1 were poured into 10mm × 10mm × 2mm molds and cured for 7 days under standard conditions. The samples were then placed in a muffle furnace and heated to 400℃ at a rate of 10℃ / min, held at that temperature for 30 minutes, and then cooled to room temperature with the furnace. The ablation residue was collected, ground into powder in an agate mortar, and after acid digestion, the Ag and Cu content in the digestion solution was analyzed using atomic absorption spectrometry.

[0079] Anti-mildew performance test Referring to GB / T 1741-2020 "Determination of Antifungal Resistance of Paint Films" and JC / T 885-2016 "Antifungal Sealant for Building Use", the sealant was poured into a 50mm×50mm×2mm mold and cured for 7 days under standard conditions. The test pieces were placed in petri dishes containing inorganic salt culture medium. A mixed spore suspension was prepared using eight standard mold strains: *Aspergillus niger*, *Aspergillus flavus*, *Penicillium citrinum*, *Chaetoceros globosum*, *Cladosporium virgaureum*, *Brachystomum buddingum*, *Penicillium cordifolium*, and *Aspergillus terreus*, and evenly inoculated onto the test piece surface using a spray method. The petri dishes were placed in a constant temperature and humidity incubator and cultured at 28±1℃ and relative humidity ≥95%. After 28 days of culture, the antifungal resistance level was evaluated according to JC / T885-2016. For the 120-day long-term test, the culture time was extended under the same conditions, and the antifungal resistance level was observed and recorded on days 28, 56, 84, and 120. The mold resistance levels are divided into four grades: Grade 0 (no mold growth, no mold growth observed under 50x magnification), Grade 1 (trace growth, coverage area <10%), Grade 2 (small growth, coverage area 10%~30%), Grade 3 (moderate growth, coverage area 30%~60%), and Grade 4 (coverage area >60%). Three samples are tested in each group, and the worst grade is taken as the result.

[0080] Storage stability test Referencing GB / T 13477.5-2002 "Test Methods for Building Sealing Materials - Part 5: Determination of Surface Drying Time", sealant samples were sealed in aluminum tubes and aged in a 70℃ oven for 7 days. After removal and cooling to room temperature, the sealant was extruded into strips approximately 2mm thick and 50mm long under standard conditions (23±2℃, RH 50±5%), and timing was immediately initiated. Every minute, a clean, dry polyethylene film was gently touched to the surface of the strip; the time when no more sealant adhered to the film was recorded as the surface drying time. The rate of change between the aging surface drying time and the initial surface drying time was calculated. Three samples were tested in each group, and the arithmetic mean was taken.

[0081] Rapid curing performance test (1) Surface drying time Referring to GB / T 13477.5-2002, the test method is the same as the surface drying time test in Section 7.3. The samples are fresh sealant cured under standard conditions and sealant after accelerated aging at 70℃ for 7 days; the surface drying time change rate = (T after aging - T initial) / T initial × 100%.

[0082] (2) 24h deep curing depth The sealant was injected into a cylindrical mold with a diameter of 15 mm and a depth of 10 mm, and cured for 24 hours under standard conditions (23±2℃, RH50±5%). A longitudinal cut was made along the center of the mold using a blade, and the vertical distance from the sample surface to the uncured interface inside was measured using calipers; this distance is the depth of deep curing. Five samples were tested in each group, and the arithmetic mean was taken.

[0083] Mechanical property testing Referencing GB / T 528-2009, "Determination of Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber," sealant was poured into a 2mm thick mold and cured for 7 days under standard conditions. The resulting specimens were then cut into I-shaped dumbbells. Tensile strength and elongation at break were tested using a universal testing machine at a tensile speed of 500mm / min and a mark spacing of 25mm. Five specimens were tested in each group, and the arithmetic mean was taken.

[0084] Data for each embodiment and comparative example are shown in Tables 5-8.

[0085] Table 5 Fire resistance performance test data

[0086] As shown in Table 5, the ceramicization initiation temperature of Example 3 is as low as 380℃, the flexural strength after ablation at 400℃ reaches 4.8MPa, the limiting oxygen index reaches 36.2%, and the vertical burning rating reaches FV-0. Among all the samples, the overall fire resistance performance is the best.

[0087] The ceramization initiation temperature of Examples 1-3 was no higher than 395℃, with Example 3 (Ag) being the highest. + and Cu 2+ Co-doped) as low as 380℃. Comparative Example 1 did not undergo Ag... + and Cu 2+ With doping, the ceramization initiation temperature reaches 520℃, the flexural strength at 400℃ is only 0.3MPa, and the limiting oxygen index is only 22.2%, indicating that Ag... + and / or Cu 2+ Doping is a necessary condition for achieving low-temperature ceramicization. Comparative Example 6 uses Ag... + With a doping concentration of 6%, the ceramization initiation temperature rises to 460℃, the flexural strength at 400℃ is only 1.2 MPa, and the limiting oxygen index is 28.3%, indicating excessive Ag. + Doping can actually hinder the ceramicization process.

[0088] Ag + and Cu 2+ Co-doping has a synergistic effect on reducing the ceramicization temperature. The ceramicization initiation temperature of Example 3 is higher than that of Ag. + Example 1, with single doping, is 15°C lower than Cu. 2+ Example 2 with single doping was 9°C lower.

[0089] It is worth noting that the vertical flammability rating of Example 1 is FV-1, slightly lower than that of Comparative Example 2 (FV-0), mainly due to the difference in gas-phase combustion behavior of the organic components (polyether segments and quaternary ammonium salts) in the functional shell under vertical flammability test conditions; however, the LOIs of the two are not significantly different, at 31.5% and 32.2% respectively, indicating that the coating of the functional shell did not have a substantial negative impact on the flame retardant efficiency of the condensed phase. This result further illustrates that the functional shell of the present invention imparts storage stability and anti-mildew properties to the sealant while having a limited impact on the core fire-retardant performance.

[0090] The ceramization initiation temperatures of Examples 4-11 are in the range of 375-392℃, the flexural strength at 400℃ is between 3.8-5.2 MPa, and the limiting oxygen index is between 34.2-37.3%, all maintaining a good level. Among them, Example 5 (40 parts of core-shell functional filler, 45 parts of reinforcing filler, and 20 parts of MDT branched silicone oil) has a flexural strength of 5.2 MPa at 400℃ and a limiting oxygen index of 37.0%; Example 11 (2 parts of phosphorus ion liquid) has a limiting oxygen index of 37.3%, indicating that when the dosage of each component is within the preferred range of the present invention, the sealant can still maintain good fire-retardant performance.

[0091] Comparative Example 8 (where the ionic liquid was added during the preparation stage of the core-shell functional filler) exhibited a flexural strength of 3.5 MPa and a limiting oxygen index of 32.5% at 400°C, lower than the 4.8 MPa and 36.2% of Example 3. This indicates that when the phosphorus-containing ionic liquid was added during the preparation stage of the core-shell functional filler, the subsequent high-temperature vacuum mixing in sealant S1 resulted in the partial loss of the phosphorus-containing ionic liquid, failing to fully exert its synergistic reinforcing effect. Comparative Example 9 (without the phosphorus-containing ionic liquid) showed a flexural strength of 3.4 MPa and a limiting oxygen index of 31.0% at 400°C, indicating that the addition of the phosphorus-containing ionic liquid had a synergistic reinforcing effect on fire resistance. Comparative Example 10 (where the phosphorus-containing ionic liquid was added after the titanium-based chelate catalyst) showed a flexural strength of only 3.0 MPa and a limiting oxygen index of 30.8% at 400°C, lower than Comparative Example 9. This indicates that without quaternary ammonium salt anchoring, the free phosphorus-containing anions poisoned the titanium-based chelate catalyst, leading to incomplete curing and a decrease in the ceramization effect.

[0092] Compared with Example 3, the fire resistance of Comparative Examples 2-5 and Comparative Example 7 showed a higher ceramization initiation temperature (12-18°C), a lower flexural strength at 400°C (1.5-2.0 MPa), and a lower limiting oxygen index (3.3-5.7%). This indicates that the fire resistance is mainly due to the Ag content of the zinc borate core layer. + and / or Cu 2+ Doping determines the effectiveness of the functional shell; changes in the coating method and structure of the functional shell have no significant impact.

[0093] Atomic absorption spectrometry analysis of the ceramization residue of the sealant sample from Example 3 after ablation at 400°C for 30 minutes revealed the presence of Ag and Cu elements, indicating that the doped Ag and Cu elements remained in the ceramization residue after high-temperature ablation. In contrast, no Ag and Cu elements were detected in the ablation residue of Comparative Example 1, further confirming that these Ag and Cu elements originated from core-layer doping. Combined with the ceramization initiation temperature data, this demonstrates that the dopant ions played a role in the high-temperature ceramization process of the sealant.

[0094] Table 6 Anti-mildew performance test data

[0095] As shown in Table 6, the anti-mold rating of Examples 1 to 11 was 0 throughout the entire cycle of 28 to 120 days, indicating that the sealant of the present invention has good long-lasting anti-mold performance.

[0096] Comparative Example 5, lacking the grafting of reactive quaternary ammonium salt, showed a mold resistance level of 2 after 28 days, which dropped to 3 after 120 days, indicating that the mold resistance of the sealant was severely insufficient when grafted with non-reactive quaternary ammonium salt. Comparative Example 4, although grafted with reactive quaternary ammonium salt, could not form a barrier coating layer due to the absence of KH-560 in the shell, resulting in a mold resistance level dropping to 1 after 84 days. This demonstrates that without effective KH-560 coating protection, the chemical grafting state of the reactive quaternary ammonium salt is difficult to maintain long-term, leading to a decline in mold resistance. Comparative Examples 1 to 3 all had a mold resistance level of 3, further demonstrating that the chemical grafting of reactive quaternary ammonium salt is key to achieving a long-lasting mold resistance level of 0.

[0097] Comparative Example 6 Ag + Increasing the doping concentration from 1.5% to 6% did not affect the anti-mold rating. Similarly, changing the molar ratio of the functional shell KH-560 to the polyether-modified silane in Comparative Example 7 from 1:1 to 3:1 also did not affect the trend of the anti-mold rating, indicating that the zinc borate core layer Ag... + The doping amount and the ratio of the functional shell KH-560 to the polyether-modified silane do not affect the antifungal function of the reactive quaternary ammonium salt. Comparative Examples 8 and 10 both had an antifungal rating of 0, indicating that the addition of phosphorus-containing liquid and its timing do not affect the antifungal function of the reactive quaternary ammonium salt. Although Comparative Example 9 did not contain phosphorus-containing liquid, its antifungal rating was still 0, further indicating that the antifungal function originates from the chemical grafting of the reactive quaternary ammonium salt.

[0098] A comparison of Comparative Example 4 and Example 3 shows that: grafting reactive quaternary ammonium salt alone is not enough to achieve long-term anti-mold effect. The functional shell of the coating structure is also needed to protect the reactive quaternary ammonium salt from environmental factors. The two work together to achieve 120-day long-term anti-mold effect.

[0099] Table 7. Test data on storage stability and rapid curing performance

[0100] (a) Storage stability analysis As shown in Table 7, the surface drying time change rate of Example 3 is at a low level. Comparative Example 2, due to the lack of functional shell coating, has a surface drying time change rate as high as 120%, with the surface drying time extended from 25 minutes to 55 minutes; Comparative Example 4, due to the absence of KH-560 in the functional shell, cannot form an effective coating, and its surface drying time change rate reaches 95%.

[0101] Comparative Example 1 was not doped with Ag + and Cu 2+However, the uncoated surface active sites of commercially available zinc borate can also lead to poisoning of the titanium-based chelate catalyst, with a surface drying time change rate much higher than that of the examples. Comparative Example 3, because its functional shell does not contain polyether-modified silane, has a surface drying time change rate between the examples and Comparative Example 2, indicating that the catalytic protection effect is limited when only KH-560 is coated without grafting reactive quaternary ammonium salts.

[0102] In Example 10, the amount of phosphorus-containing ionic liquid was 0.5 parts, and the surface drying time change rate was 12.5%; in Example 11, the amount of ionic liquid was 2 parts, and the change rate was 15.4%, indicating that the storage stability was good when the amount of ionic liquid was in the range of 0.5 to 2 parts. In Example 8, the amount of titanium-based chelate catalyst was 0.5 parts, and the surface drying time change rate was 14.3%; in Example 9, the amount of catalyst was 2 parts, and the change rate was 15.4%, indicating that the storage stability was good when the amount of catalyst was in the range of 0.5 to 2 parts. A complete functional shell structure combined with an appropriate amount of titanium-based chelate catalyst is key to achieving excellent storage stability.

[0103] The surface drying time change rate of Comparative Example 8 was 66.7%, which was significantly higher than that of Example 3 (14.3%). This indicates that when the phosphorus-containing ionic liquid was added during the preparation stage of the core-shell functional filler, the high temperature vacuum of S1 caused some loss of the phosphorus-containing ionic liquid and it was not effectively anchored by the quaternary ammonium salt. The residual free phosphorus-containing ionic liquid poisoned the catalyst during storage, resulting in a decrease in the crosslinking reaction activity, which in turn significantly extended the surface drying time after aging from 15 minutes to 25 minutes.

[0104] The surface drying time change rate of Comparative Example 10 was as high as 122.2%, with the surface drying time extending from 18 minutes to 40 minutes, the highest among all samples. This indicates that when the phosphorus-containing ionic liquid is not anchored by a quaternary ammonium salt, the free phosphorus-containing anions directly coordinate and poison the titanium-based catalyst, severely deteriorating its storage stability. The surface drying time change rate of Comparative Example 9 was 13.3%, indicating that the catalyst does not face the risk of being poisoned by the ionic liquid without it. However, its curing depth (5.0 mm) was lower than that of Example 3 (5.5 mm), further demonstrating that the timing of the addition of the phosphorus-containing ionic liquid is crucial to achieve both enhancement and maintain storage stability.

[0105] (II) Rapid Curing Analysis As shown in Table 7, Comparative Example 3, lacking polyether-modified silane in its functional shell, exhibited the longest surface drying time and the shallowest 24-hour deep curing depth, indicating that the hydrophilic polyether segments of the polyether-modified silane play a decisive role in improving water wetting, penetration, and inward diffusion. Comparative Example 7, with its insufficient proportion of polyether-modified silane in its functional shell, showed significantly weaker rapid curing than Example 3, demonstrating that the ratio of polyether-modified silane to KH-560 directly affects the rapid curing effect. The curing speeds of Comparative Examples 2 and 4 were also slower than that of Example 3, further illustrating that the structural integrity of the functional shell is one of the important factors affecting water penetration and diffusion efficiency.

[0106] When the amount of crosslinking agent was 2 parts (Example 6), 5 parts (Example 3), and 8 parts (Example 7), the surface drying time of the sealant was 14 min, 14 min, and 13 min, respectively, and the deep curing depth after 24 hours was 5.1 mm, 5.5 mm, and 5.8 mm, respectively. As the amount of crosslinking agent increased, the surface drying time was slightly shortened and the curing depth was slightly increased.

[0107] The 24-hour deep curing depth of Comparative Example 9 was 5.2 mm, lower than the 5.5 mm of Example 3, indicating that the addition of phosphorus-containing ionic liquid improved the curing depth. The 24-hour curing depth of Comparative Example 8 was 4.3 mm, and that of Comparative Example 10 was 4.1 mm, further demonstrating that the phosphorus-containing ionic liquid must be added before the addition of the titanium-based chelate catalyst and anchored by the quaternary ammonium salt to fully exert its curing-promoting effect.

[0108] Table 8 Mechanical Performance Test Data

[0109] The tensile strength of each embodiment is 2.3~3.5MPa, and the elongation at break is 280%~400%, meeting the requirements for indoor home decoration sealant (tensile strength ≥0.5MPa, elongation at break ≥150%). Examples 1-3 use Ag, respectively. + Doping, Cu 2+ Doping and Ag + and Cu 2+ The tensile strengths of the Ag-doped products were 2.3 MPa, 2.8 MPa, and 3.2 MPa, respectively, and the elongation at break were 400%, 360%, and 320%, respectively, indicating that Ag... + and Cu 2+ Co-doping increases tensile strength but reduces elongation at break.

[0110] In Examples 3-5, the total amounts of core-shell functional filler and reinforcing filler were 65 parts, 45 parts, and 85 parts, respectively, with tensile strengths of 2.8 MPa, 2.5 MPa, and 3.5 MPa, and elongation at break of 360%, 380%, and 280%, respectively. This indicates that increasing the total amount of filler increases tensile strength but decreases elongation at break.

[0111] The tensile strength of Comparative Example 6 was 2.2 MPa, lower than that of Example 3 (3.2 MPa); the elongation at break was 330%, higher than that of Example 3 (320%), indicating an excess of Ag. + The doping of the zinc borate core layer reduces tensile strength. The tensile strength of Comparative Example 2 is 2.0 MPa, which is lower than that of Example 3 (3.2 MPa), indicating that the interfacial bonding force between the core-shell functional filler and the sealant is weak when there is no functional shell coating, resulting in a decrease in mechanical properties.

[0112] The tensile strengths of Comparative Examples 8-10 were 2.5 MPa, 2.6 MPa, and 2.4 MPa, respectively, all lower than those of Example 3, further demonstrating that the addition of phosphorus-containing ionic liquid and the correct timing of addition play an important role in maintaining good mechanical properties.

[0113] in conclusion The fire-retardant, mildew-resistant, and alcohol-free type one-component silicone sealant prepared in Examples 1-11 of this invention has a ceramization initiation temperature ≤395℃, a flexural strength ≥3.0MPa after ablation at 400℃, and a flame retardant rating of FV-0 to FV-1; its mildew resistance rating remains at level 0 after 120 days; the surface dryness time change rate is ≤16% after 7 days of accelerated aging at 70℃; the deep curing depth is ≥4.5mm after 24 hours; the tensile strength is ≥2.3MPa, and the elongation at break is ≥280%. Comparative data show that the Ag-doped sealant... + and / or Cu 2+ The zinc borate core layer is essential for achieving low-temperature ceramization of the sealant; the functional shell layer is key to storage stability; the polyether-modified silane is crucial for rapid curing; reactive quaternary ammonium salt chemical grafting is fundamental for long-lasting mildew resistance; and the addition of phosphorus-containing ionic liquid before the addition of the titanium-based chelate catalyst is an effective way to achieve synergistic flame retardant enhancement. This invention achieves relatively rapid deep curing while also possessing excellent fire resistance, mildew resistance, and storage stability, making it suitable for sealing joints in indoor kitchens, bathrooms, balconies, and other home decoration scenarios.

[0114] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant, characterized in that, By weight, it includes the following components: 100 parts of alkoxy-terminated polydimethylsiloxane, 10-20 parts of MDT branched silicone oil, 20-40 parts of core-shell functional filler, 25-45 parts of reinforcing filler, 0.5-2 parts of phosphorus-containing ionic liquid, 2-8 parts of crosslinking agent, 0.5-2 parts of titanium-based chelate catalyst, 0.5-5 parts of silane coupling agent, and 0.5-3 parts of hydroxyl scavenger; The phosphorus-containing ionic liquid is 1-ethyl-3-methylimidazolium dibutyl phosphate; the core-shell functional filler is a core-shell structured particle, comprising, from the inside out, doped with Ag. + and / or Cu 2+ The core consists of a zinc borate core layer and a functional shell layer covering the surface of the core layer; the functional shell layer is formed by the co-condensation of polyether-modified silane and KH-560; the surface of the functional shell layer is chemically grafted with a reactive quaternary ammonium salt; the phosphorus-containing ionic liquid is anchored to the surface of the core-shell functional filler by forming ion pairs with the cations of the reactive quaternary ammonium salt through its anions.

2. The fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant according to claim 1, characterized in that, In the zinc borate core layer, Ag + The doping amount is Zn 2+ 0.5-3% molar amount of Cu 2+ The doping amount is Zn 2+ The molar amount is 1-5%; the particle size of the zinc borate core layer is 1-10 μm.

3. The fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant according to claim 1, characterized in that, The reactive quaternary ammonium salt achieves chemical grafting through the condensation of its alkoxysilane groups with residual hydroxyl groups on the surface of the functional shell.

4. The fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant according to claim 1, characterized in that, The reactive quaternary ammonium salt is 3-(trimethoxysilyl)propyldimethyloctadecylammonium chloride.

5. The fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant according to claim 1, characterized in that, The polyether-modified silane is prepared by a ring-opening reaction of terminal epoxy polyether and aminosilane. The molecular weight of the terminal epoxy polyether is 400-2000, and the aminosilane is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

6. The fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant according to claim 1, characterized in that, The alkoxy-terminated polydimethylsiloxane has a viscosity of 5000~80000 mPa·s at 25°C; the MDT branched silicone oil has a viscosity of 100~2000 mPa·s.

7. The fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant according to claim 1, characterized in that, The reinforcing filler is fumed silica and / or precipitated silica with a specific surface area of ​​100~400 m². 2 / g; the crosslinking agent is selected from at least one of methyltrimethoxysilane, phenyltrimethoxysilane, tetraethyl orthosilicate and its oligomers; the titanium chelate catalyst is diisopropoxybis(acetylacetone)titanium, diisopropoxybis(ethylacetoacetic acid)titanium or a chelate of tetrabutyl titanate and acetylacetone; the silane coupling agent is selected from at least one of γ-glycidoxypropyltrimethoxysilane and γ-methacryloyloxypropyltrimethoxysilane; the hydroxyl scavenger is selected from at least one of hexamethyldisilazane, trimethylchlorosilane, and vinyltrimethoxysilane.

8. A method for preparing a core-shell functional packing material, characterized in that, Includes the following steps: (1) Disperse zinc borate in silver salt and / or copper salt solution, and carry out ion exchange reaction at 30~80℃ for 2~8 hours. After washing, drying and grinding, obtain Ag-doped solution. + and / or Cu 2+ The zinc borate core layer; (2) Disperse the zinc borate core layer obtained in step (1) in an alcohol-water mixed solvent, add polyether modified silane and KH-560, and carry out hydrolysis and condensation reaction at 40~80℃ for 2~6 hours. After washing, drying and grinding, obtain the functional shell layer coated on the surface of the zinc borate core layer. (3) Disperse the functional shell obtained in step (2) in an organic solvent, add a reactive quaternary ammonium salt, and carry out a grafting reaction at 50~100℃ for 4~12 hours. After washing, drying and grinding, a core-shell functional filler with reactive quaternary ammonium salt chemically grafted on the surface of the functional shell is obtained.

9. The method for preparing the core-shell functional packing material according to claim 8, characterized in that, In step (2), the molar ratio of polyether-modified silane to KH-560 is (0.3~2):

1.

10. A method for preparing a fire-retardant, mildew-resistant, alcohol-free type one-component silicone sealant, characterized in that, Includes the following steps: S1. Add alkoxy-terminated polydimethylsiloxane, MDT branched silicone oil, core-shell functional filler prepared by the method of claim 8, and reinforcing filler to a kneader, and knead and dehydrate for 2-4 hours at 100-150°C and vacuum degree of -0.08--0.095MPa, and cool to room temperature to obtain base material; S2. Under nitrogen protection, add crosslinking agent, silane coupling agent and hydroxyl scavenger to the base material obtained in step S1, and mix at 20~40℃ for 10~40 minutes. S3. Add phosphorus-containing liquid and stir for 0.5 to 1 hour under normal or slightly negative pressure at 30 to 50°C; S4. Add titanium-based chelate catalyst, and continue stirring for 0.5 to 2 hours under a vacuum of -0.08 to -0.095 MPa. Discharge and fill to obtain fireproof, mildew-proof, alcohol-free type one-component silicone sealant.